The effect of low-density background plasma on frequency and energy characterictics of coaxial gyrotron cavity - Moskvitina, Yu.K.; Zaginaylov, G.I.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2012)
The effect of low density background plasma on the electromagnetic field energy density in the ITER relevant coaxial gyrotron cavity is studied. The model of cold collisionless magnitoactive plasma is used. The dispersion relation and expression for the density of RF energy in plasma-filled coaxial gyrotron cavity are derived in the analytical form and analyzed numerically. It is shown that presence of low density plasma in coaxial gyrotron cavity leads to downshift of the operational frequency and to decreasing Ohmic loads of both the outer and inner conductors of coaxial gyrotron cavity. Изучено влияние фоновой плазмы низкой плотности на плотность энергии электромагнитного поля в коаксиальном резонаторе гиротрона ITER. Используется модель бесстолкновительной, магнитоактивной плазмы. Дисперсионное соотношение и выражение для плотности СВЧ-энергии в плазмонаполненном коаксиальном резонаторе гиротрона получены аналитически и исследованы численно. Показано, что наличие плазмы низкой плотности в коаксиальном резонаторе гиротрона приводит к уменьшению рабочей частоты и уменьшению омических потерь на внешней стенке и внутреннем проводнике резонатора коаксиального гиротрона. Вивчено вплив фонової плазми низької щільності на густину енергії електромагнітного поля в коаксіальному резонаторі гіротрона ITER. Використовується модель беззіткненної, магнітоактивної плазми. Дисперсійні співвідношення та вираз для густини НВЧ-енергії в плазмонаповненому коаксіальному резонаторі гіротрона отримані аналітично та досліджені чисельно. Показано, що наявність плазми малої густини в коаксіальному резонаторі гіротрона призводить до зменшення робочої частоти та зменшення омічних втрат на зовнішній стінці та на внутрішньому провіднику резонатора коаксіального гіротрона.